New Approaches to Optimize Somatic Embryogenesis in Maritime Pine - Arrillaga, Isabel; Morcillo, Marian; Zanón, Israel; Lario, Francisco; Segura, Juan; Sales, Ester (Frontiers in Plant Science, 2019)
Maritime pine (Pinus pinaster Aiton) is a coniferous native of the Mediterranean basin. Because of its adaptability to a wide range of environmental conditions, the species have become a model for studies in coniferous forest management and functional genomics. Somatic embryogenesis (SE) has been so far, the preferred strategy for maritime pine breeding programs initiated at the middle-end of the twentieth century. To overcome the limitations of the induction and maturation phases in maritime pine SE, we analyzed the possible maternal influence on the embryogenic capability of megagametophytes from controlled crosses, as well as the effect of the temperature and water availability during SE process on the production of plants. A strong maternal effect on the embryogenic potential of maritime pine megagametophytes was observed in our experiments using half-sib and full-sib progenies, while paternal effect was almost undetectable. Besides, it seems possible to improve somatic embryo production of maritime pine megagametophytes by adjusting optimal temperature throughout the process: 28ºC during induction and proliferation, and 23ºC during the maturation phase. Using media with reduced water availability (6 g/L Gelrite) can also increase embryo production. Since other limitation of maritime pine SE is culture decline of embryogenic masses (EMs), that reduces embryo yield and germination, we assessed the profile of ABA and IAA and the expression of two embryogenesis-related genes (LEC1 and WOX2) during maturation of EMs of two morphotypes that differed in their maturation capability. Spiky morphotype, with high maturation capability, had a steady increase in both hormones along the 12 weeks of the maturation, whereas ABA content in smooth morphotype picked at the 4th week and dropped. EMs with this morphotype also had a higher IAA content at the beginning of the maturation. A decrease of LEC1 and WOX2 gene expression over the course of embryo development was found to be characteristic of the spiky morphotype with high maturation capability.